Longitudinal characterization of mild cognitive impairment and dementia in World Trade Center responders at midlife. (31st December 2021) - Clouston, Sean A.P.; Mann, Frank P; Diminich, Erica D; Kritikos, Minos; Pellecchia, Alison; Mejia‐Santiago, Stephanie; Carr, Melissa; Kotov, Roman; Gandy, Samuel; Sano, Mary; Bromet, Evelyn; Luft, Benjamin J
Abstract: Background: Though the Montreal Cognitive Assessment (MoCA) is validated for cross‐sectional assessment, there is limited guidance as to methods for reliably identifying incident cases of Mild Cognitive Impairment (MCI) and dementia. The goal of this study was to examine characteristics of individuals identified as having MCI and dementia using different diagnostic routines. Methods: World Trade Center (WTC) responders are a unique population, not only because of the historic significance of the traumatic exposures many endured while onsite following the terrorist attacks in New York City on 9/11/2001 but also given responders participation in a long‐term monitoring program established by the Centers for Disease Control (CDC) in 2002 to monitor the long‐term effects of WTC exposures on health outcomes. Since 2014, we have administered the MoCA to responders over at least three assessments ( n =2, 370). The MoCA was administered by trained research staff; alternate versions were used to account for learning. Seven diagnostic routines were examined that variably examined adjusting for learning, objective evidence of functional limitations, and cognitive decline to identify one with the least variability in outcome. Stability of diagnostic outcome was the primary outcome. Follow‐up studies in subsets of the population included a detailed computer‐assisted neuropsychological examination, measures of physical functional limitations, a cross‐sectional sample of plasma based biomarkers measured using Simoa (e.g., b‐Amyloid1‐40, b‐Amyloid1‐42, Total‐Tau, Glial Fibrillary Acidic Protein, and Neurofilament‐Light), a cross‐sectional assessment of cortical thickness, and a self‐reported version of the Mild Behavioral Checklist. Results: 8.0% of responders were male, 4.3% were Black, and 7.7% were Hispanic. The mean age at initial MoCA assessment was 52.6 years old (SD=8.1). There was enormous variability in longitudinal stability in MCI and dementia diagnostic outcomes between different longitudinal diagnostic routines (Spearman's r =0.22‐0.86). Though domain‐specific sub‐scales with high internal consistency (a=0.92‐0.97) were available, the most stable definition relied on MoCA scores adjusted for learning and expected within‐person test‐retest score distributions. MCI and dementia identified using all diagnostic routines were variably associated poorer cognitive functioning and with biomarkers. Conclusion: This study gives guidance about differences between methods relying on the MoCA to longitudinally screen WTC responders for MCI and dementia at midlife.